Monoclonal Gammopathies of Clinical Significance—Scleromyxedema: A Case Report and Literature Review - Shanshan Liang; Jingjing Zeng; Peiying Zhong; Chengyao Jia; Li Zhang (Clinical Case Reports)
ABSTRACT Scleromyxedema is an uncommon, chronic connective tissue disorder with an obscure etiology. It is distinguished by fibromyxoid skin lesions and elevated serum monoclonal immunoglobulin levels. The condition's rarity limits epidemiological data, making prevalence and incidence assessment difficult. Herein, we detail a clinical case of scleromyxedema, encompassing diagnosis and treatment, to augment medical understanding of this rare entity. The aim of this study is to delve into the complexities of diagnosing scleromyxedema, encompassing its diverse clinical presentations, with the goal of refining diagnostic acumen and expediting the identification process. This, in turn, mitigates the risks associated with diagnostic delays. Moreover, the imperative of instituting pertinent therapeutic measures is highlighted as a fundamental aspect of patient management, underscoring the significance of a tailored approach to treatment. Concurrently, this endeavor demands rigorous precision from clinical laboratory staff. The accurate provision of laboratory data is essential to prevent oversights and misinterpretations in diagnosing this rare condition.